Exploring nature-based interventions as an ecosocial method in social work: insights from Ireland, Finland and Italy - Conway, Rebecca; Obeng, James Kutu; Nassar, Areen; Mansueto, Mattia (Policy press, 2025)
This chapter looks at nature-based interventions (NBIs) as an ecosocial method within social work to address complex challenges faced by individuals in precarious situations. Through case studies from Ireland, Finland and Italy, it examines how NBIs – including equine-assisted services, outdoor youth activation workshops and green care services – promote social inclusion, mental wellbeing and community cohesion. The findings from the case studies demonstrate the benefits of integrating nature into social work practice, highlighting improvements in health and wellbeing, learning, self-determination and social relationships. The chapter also critically reflects on the limitations of NBIs, including methodological challenges and concerns about their structural impact. Ultimately, it argues that NBIs offer a promising approach to holistic wellbeing and sustainability within social work, advocating for their ethical and context-specific application in future social work practice, education and research.